1996
DOI: 10.1177/017084069601700404
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentation and Transformation in Organizational Change: The Case of Canadian Law Firms

Abstract: This paper identifies two archetypes in large Canadian law firms to show how ideas of professionalism and partnership are changing, due in part to shifts in discourses in the wider institutional context. These changes in discourse themselves alter the interpretation of organizational structures and systems. This theme is explored through the concept of tracks and sedimentation. We explore the emergence of an organizational archetype that appears not to be secure, and which results in sedimented structures with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
466
3
19

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(496 citation statements)
references
References 18 publications
8
466
3
19
Order By: Relevance
“…The institutional school of thought on coordination suggests that coordination failure can be avoided not just by means of formal and explicit rules, but also by means of informal norms and implicit assumptions derived from broad societal institutions (DiMaggio, 1997) or more industry-, profession-, or organization-specific institutions (Bechky, 2003;Cooper, Hinings, Greenwood, & Brown, 1996;Cooper, Rose, Greenwood, & Hinings, 2000;Tilcsik, 2010). These cultural influences can inform individuals' perceptions of task interdependencies (Steensma, Marino, Weaver, & Dickson, 2000) and their interpretation of the level and impact of external uncertainties (Daft & Weick, 1984).…”
Section: The Coordination Perspectivementioning
confidence: 99%
“…The institutional school of thought on coordination suggests that coordination failure can be avoided not just by means of formal and explicit rules, but also by means of informal norms and implicit assumptions derived from broad societal institutions (DiMaggio, 1997) or more industry-, profession-, or organization-specific institutions (Bechky, 2003;Cooper, Hinings, Greenwood, & Brown, 1996;Cooper, Rose, Greenwood, & Hinings, 2000;Tilcsik, 2010). These cultural influences can inform individuals' perceptions of task interdependencies (Steensma, Marino, Weaver, & Dickson, 2000) and their interpretation of the level and impact of external uncertainties (Daft & Weick, 1984).…”
Section: The Coordination Perspectivementioning
confidence: 99%
“…multinational clients, cross-border projects and the internationalization of legal business), a further strand of significance to this research addresses 'archetype shift' in PSFs (Greenwood & Hinings, 1993Morris & Pinnington, 1998Pinnington & Morris, 2002) and in law firms (Cooper et al, 1996;Pinnington & Morris, 2003;Brock, 2006). 'Archetype shift' means that the traditional hierarchical professional partnership (usually called the 'P 2 ' structure (Greenwood et al, 1990)) has changed into a more 'business-like' entity (Pinnington & Morris, 2003: 85) known as the 'managed professional business' (MPB).…”
Section: The Growing Globalization Of Law Firmsmentioning
confidence: 99%
“…Some studies have shown how accounting practices can be mobilized by organizational actors to introduce a new order and model of organizational rationality, typically one focused on market concerns (e.g., Dent, 1991;Oakes, Townley & Cooper, 1998;Ezzamel, Willmott & Worthington, 2008). Other research has emphasized the role of accounting in situations of multiple and potentially conflicting interests, logics and regimes of accountability (e.g., Cooper, Hinings, Greenwood & Brown, 1996;Ahrens & Chapman, 2002;Lounsbury, 2008). In these settings, organizational subgroups can hold differing views of organizational reality that are not displaced, but can become layered (c.f., Cooper et al, 1996) such that they persist over time, or, as the quote above suggests, remain "divided down the middle."…”
Section: Introductionmentioning
confidence: 99%
“…Other research has emphasized the role of accounting in situations of multiple and potentially conflicting interests, logics and regimes of accountability (e.g., Cooper, Hinings, Greenwood & Brown, 1996;Ahrens & Chapman, 2002;Lounsbury, 2008). In these settings, organizational subgroups can hold differing views of organizational reality that are not displaced, but can become layered (c.f., Cooper et al, 1996) such that they persist over time, or, as the quote above suggests, remain "divided down the middle." Here, accounts such as costing, resource allocation, and performance measurement systems are involved in on-going contests and struggles as various groups advance particular interests and values (e.g., Nahapiet, 1988;Briers & Chua, 2001;Andon, Baxter & Chua, 2007).…”
Section: Introductionmentioning
confidence: 99%